IMPACT OF THE WHISTLEBLOWING POLICY IN THE FIGHT AGAINST CORRUPTION IN NIGERIA - NIMCHAK NANSAK EMMANUEL; MOSES DANJUMA BOT (International Studies Journal)
The menace of corruption and its corrosive effects on the Nigerian people and polity is pervasive and obvious throughout her history. These fatal effects corruption has produced and will continue to produce if left unchecked, has propelled successive Nigerian governments to devise strategies and policies to decisively tackle corruption with the aim of reducing it as much as possible. The necessitating factor for this research, however, is that despite these efforts, the problem of corruption still persists in Nigeria with insinuations that it is getting even worse. This study, therefore examines the impact of the whistle-blowing policy on the fight against corruption in Nigeria; From the findings of this work, the whistle blowing policy has not had the desired impact on the country’s anti-corruption crusade. This work, therefore, recommends, among other things, that the whistle blowers should be given adequate legal and security protection and adequate public awareness be embarked upon to educate the people of the need to expose corrupt individuals.